Peranan Bank Wakaf Mikro dalam Pemberdayaan Ekonomi Masyarakat di Purwokerto - Syarif Hidayat; M Makhrus (Jurnal Ilmiah Ekonomi Islam, 2021)
This article aims to determine the role of the Micro Waqf Bank in the economic empowerment of the community in Purwokerto by optimizing the management of productive waqf. This type of research is qualitative descriptive with data collection techniques of interviews, observation, and documentation. Data analysis was carried out through synchronization between the research data and the theory that would support the conclusions of this study. The results of this study indicate that the role of community economic empowerment carried out by BWM Amanah Berkah Nusantara is through the provision of micro-business financing to poor people who have businesses or people who intend to have a business. The financing is given at a predetermined nominal according to the business priority scale and without the use of collateral. Communities who receive financial assistance are provided assistance in developing religious businesses and guidance, so that empowerment activities can have an economic and spiritual impact.